Pengukuran Sistem Informasi Menggunakan Metode Function Point (FP) pada Siakad Universitas XYZ - Elok Tiara Cahya Septi; Firdayatul Dewi Sartika; Renny Sari Dewi (STMIK Budi Darma, 2020)
Software cost calculation is an activity carried out to determine the value of a software using a quantitative approach. Seeing that there are various measurement methods and there are still no standards in assessing software, this measurement process is ignored, even though this process has a strategic role in software development. This research intends to calculate the size of the business of developing academic information system software with the Function Point (FP) method. The steps taken are (1) calculating the amount of function points, (2) calculating the software development effort, and (3) distributing the amount of effort to each activity. The results of this study are efforts to develop an academic information system is 1,460 people / hour and the nominal amount is IDR 177,917,997.